The dynamic formation of low-dimensional inorganic nanotubes by filling carbon nanotubes. - Wilson, M (2009)
The filling of groups of carbon nanotubes (CNTs) by a generic molten salt of stoichiometry MX is observed using molecular dynamics computer simulation. The CNTs are grouped in terms of their diameters. The salt fills the CNTs to yield low-dimensional inorganic NT (INT) structures whose morphologies can be understood with reference to the folding of a sheet of percolating hexagons. The use of a relatively simple model to describe the interatomic interactions allows multiple filling events to be observed from the same pressure-temperature state point and so permits a rudimentary statistical analysis (often lacking in experimental investigation) of the formed INT morphologies in terms of fundamental CNT properties. The filling events are characterized in terms of the obtained INT morphologies. The thermodynamic and kinetic factors controlling the INT formation, including potential control over their morphology, are discussed. Kinetics (mechanistic) control is found to be significant compared with entropic effects. The role of the CNTs is discussed in terms of behavior as energy landscape filters. The results indicate that a complete morphological control over INTs formed in this fashion may be problematic even if the encasing CNT morphology can be strongly controlled.